Information Systems/Information Technology Strategic Planning Using the Open Group Architecture Framework Development Method - Aziz, Muhammad Rifqi; Rudianto, Christ; Chernovita, Hanna Prillysca (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
CV. Suien Insan Persada is a wood processing company whose production uses logs as the starting material. The wood is then processed into wood sheets for furniture manufacturing companies and shipped overseas. This wood industry is located in Kab. Boyolali, Central Java. CV. Suien Insan Persada has not used adequate information technology. Data processing carried out by the production department produces manual reports that are given and managed directly by the administration section. This method makes filing more difficult to manage because manual reports in the form of writing on paper are easily damaged, and there is a risk of data being lost. The problems that occur in CV. Suien Insan Persada needs a solution to make CV easier. Suien Insan Persada in making a report to resolve the above problems. The solution to overcome the problem is utilizing Information Technology (IT) with a good strategic plan by creating an information system architecture in the form of TOGAF ADM. TOGAF ADM was chosen because it has a detailed and open-source framework that can be used by CV. Suien Insan Persada to build an Enterprise Architecture (EA) that suits the needs. Besides that, TOGAF has the advantage of being flexible and open source. The results showed that TOGAF ADM could produce IS/IT strategic plan documents expected to solve the problems faced by CV. Suien Insan Persada.